1981
DOI: 10.1203/00006450-198101000-00097
|View full text |Cite
|
Sign up to set email alerts
|

Basal and TRH induced thyreotropin in neutral goiter: dependence upon duration of illness, lack of response in 3 out of 62 patients

Abstract: Stimulation of growth hormone by oral clonidine. We don't have the ideal test wich permit us know the pituitary reserve of GH.We studied the effect of the clonidine in 1 6 healthy children whose ages were from 6-15 years old and in 3 with hypopituitarism. The dose used was of 0.005 mgfkg given orally.We obtained blood samples to measure the GH (in the normal children samples were also taken for glucose in ten of them, and for insulin, TSH and prolactin in all of them) at 0, 4 0 , 6 0 , 90, 1 2 0 , and 1 4 0 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
1981
1981

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Delange et al [3] found that, in case of endemic goiter in humans, there is no correlation between TSH level in blood serum and the thyroid size and function. Romer et al [20] have reported that the increase of TSH concentration level has no significance in the pathomechanism of neutral goiter formation in children. Naeije et al [17] have proved that in the con ditions of experimental iodine deficiency in rats the thyroid enlargement takes place, which is at first, accompanied by a nonincreased TSH level in blood serum.…”
Section: Discussionmentioning
confidence: 99%
“…Delange et al [3] found that, in case of endemic goiter in humans, there is no correlation between TSH level in blood serum and the thyroid size and function. Romer et al [20] have reported that the increase of TSH concentration level has no significance in the pathomechanism of neutral goiter formation in children. Naeije et al [17] have proved that in the con ditions of experimental iodine deficiency in rats the thyroid enlargement takes place, which is at first, accompanied by a nonincreased TSH level in blood serum.…”
Section: Discussionmentioning
confidence: 99%